Análise da influência das estratégias circulares na inovação do modelo de negócios circular e no desempenho empresarial das indústrias químicas brasileiras - Motke, Francies Diego (2023)
The search for sustainability in business starts with the implementation of circular strategies, putting an end to the current linear production system. For this, developing a business model in accordance with the principles of the circular economy, adjusting production cycles for maximum efficiency in the use of resources, can guarantee returns that exceed those provided by circular strategies. It is therefore necessary for companies to innovate in their business model for a circular model and, with that, create enough value to increase their performance. With this, this study aims to analyze the influence of circular strategies on the innovation of the circular business model and on the business performance of the Brazilian chemical industries. The research was designed from a quantitative approach, of a descriptive nature, through a survey. The questionnaires were sent online to Brazilian chemical industries associated with Abiquim between January and July 2021, with 56 companies returning. The results reveal that there are positive associations between circular strategies with circular business model innovation and business performance. It was also possible to observe that companies that present a degree of radical innovation of the circular business model and a higher level of business performance also present greater adherence in the implementation of circular strategies. Finally, it was shown that the strategies of less use of inputs and natural resources and maintaining the value of products, components and materials discriminate the groups of industries with an incremental degree and a radical degree of innovation of the circular business model, while the lowest use of inputs and natural resources, less loss of materials and waste, and maintaining the value of products, components and materials determine the groups of industries with a higher or lower level of business performance.